Stationarity disturbance monitoring planning of the flow of waste emissions at a fixed observation time - Любимова, Нина Александровна (Technology audit and production reserves, 2016)
This article examines the stationarity disturbance monitoring planning of the flow of multicomponent pollution of flue gases of thermal power plants on local observation intervals. A characteristic feature of the considered monitoring process is a priori uncertainty, stationarity disturbance by mathematical expectation, dispersion and spectrum simultaneously constituting pollution. The limited observation time and economic costs of monitoring procedures brings additional difficulties in the condition of performing routine requirements to the monitoring. Monitoring planning of the flue gas flow control should take into account not only the volume of the sample, but also the order of their carrying out. It was proposed the method of non-stationarity parameter assessment by introducing preventive control of borders separately for each component of flue gas pollution. Evaluation of stationary pollution processes can reduce the prior uncertainty in the monitoring planning and rank the pollutants in the degree of reducing the risk of their occurrence. This will perform maintenance standards and take into account the risk monitoring of the 1st and 2nd kind. This approach is useful when monitoring planning of a multi-component pollution, when it is necessary to determine the priority pollutant for a degree of stationary disturbances in local time intervals.